2020
DOI: 10.1002/ece3.5949
|View full text |Cite
|
Sign up to set email alerts
|

Environmental influences on and antimicrobial activity of the skin microbiota of Proceratophrys boiei (Amphibia, Anura) across forest fragments

Abstract: The composition of the skin microbiota of amphibians is related to the biology of host species and environmental microbial communities. In this system, the environment serves as a microbial source and can modulate the hosted community. When habitats are fragmented and the environment disturbed, changes in the structure of this microbial community are expected. One important potential consequence of fragmentation is a compromised protective function of the microbiota against pathogenic microorganisms. In this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 47 publications
(48 reference statements)
1
8
0
Order By: Relevance
“…In addition, the relative abundance of certain bacterial taxa on the skin of both life stages differed between the two habitat types. These microbiome changes are congruent with other studies with different taxa assessing the effects of environmental changes (e.g., the gut microbiota of Darwin’s finches in the Galapagos islands [ 42 ]) [ 11 , 18 , 42 ]. It is known that human activities have an impact on the abiotic conditions of the environment affecting the diversity of host bacterial communities.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In addition, the relative abundance of certain bacterial taxa on the skin of both life stages differed between the two habitat types. These microbiome changes are congruent with other studies with different taxa assessing the effects of environmental changes (e.g., the gut microbiota of Darwin’s finches in the Galapagos islands [ 42 ]) [ 11 , 18 , 42 ]. It is known that human activities have an impact on the abiotic conditions of the environment affecting the diversity of host bacterial communities.…”
Section: Discussionsupporting
confidence: 88%
“…This means that it can threaten the survival of individuals and the growth of populations due to a cascade of negative health effects [ 10 13 ]. In fact, several recent studies have documented how skin and gut microbiomes from different wildlife species can be sensitive to habitat fragmentation and contaminants attributed to human activities [ 14 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The environment acts as a major driving force for host–microbe interactions [ 2 , 4 , 33 , 35 , 36 ]. In the present work, the composition of the skin cultivable microbiota of Perez’s frog was studied by cultivation methods.…”
Section: Discussionmentioning
confidence: 99%
“…Amphibians are a group of vertebrates that harbor a rich and diverse microbiome on their skin [ 1 , 2 , 3 ]. It has been shown that this cutaneous microbiota may play an important role as a complement to the innate immune system of amphibians, by acting as a physical barrier, through the production of antimicrobial substances or even by stimulating the host immune system [ 4 , 5 ]. Amphibians colonized all continents (except Antarctica) with more than 7000 species, known nowadays [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation